Chronic disseminated intravascular coagulation presenting as renal mass - Somashekhar Manjiri; Kadamba Padmalatha; Wakodkar Mugdha (Wolters Kluwer Medknow Publications, 2008)
Disseminated intravascular coagulation (DIC) is a complex clinical syndrome, described as a sequential activation of the coagulation and fibrinolytic system. Trauma and sepsis are some of the known precipitating factors. We report a case of nonovert disseminated intravascular coagulation presenting as a huge renal mass in a 3-year-old child, suspected to be a Wilms′ tumor. On imaging studies, it was found to be a renal hematoma. Laboratory investigations revealed an underlying chronic disseminated intravascular coagulation caused by sepsis. The child recovered with conservative treatment; follow up investigations showed resolution of renal hematoma with renal function returning to base line. Clinical presentation of Chronic DIC is variable. Laboratory investigations usually help to diagnose the condition and also to monitor the progress of the treatment. The treatment of the triggering cause is the cornerstone of the management of this condition.